Neglected Care Leading to Generalised Tuberculosis Verrucosa Cutis in a 25-Year-Old Immunocompetent Patient: A Rare Case Report from Bangka Belitung and Literature Review - David Herryanto; Andriansyah Bonorusid (The International Journal of Medical Science and Health Research, 2025)
Introduction: Tuberculosis (TB) remains a significant global health issue. Cutaneous tuberculosis (CTB) is a rare extrapulmonary manifestation, accounting for only 1–2% of all extrapulmonary TB cases. Tuberculosis verrucosa cutis (TVC) is a unique, paucibacillary form of CTB, typically presenting as a solitary lesion in a previously sensitised individual with good immunity. Generalised TVC in an immunocompetent patient is an exceptionally rare presentation and poses a considerable diagnostic challenge. Case Illustration: A 25-year-old, immunocompetent male patient presented with a 20-year history of progressive, painful verrucous skin lesions. The condition began as a single papule on his knee at age 5 and gradually disseminated to involve nearly the entire body surface, including the trunk, extremities, head, and all 20 nails (total onychodystrophy). Laboratory investigations revealed significant neutrophilic leukocytosis and progressive anaemia of chronic disease, Laboratory investigations revealed significant neutrophilic leukocytosis, progressive anaemia of chronic disease, and normal baseline liver and kidney function, while serology for HIV was negative. A chest radiograph showed no evidence of active pulmonary tuberculosis, pointing towards an exogenous inoculation form of the disease. Literature Review and Discussion: TVC results from the exogenous inoculation of Mycobacterium tuberculosis into the skin of an individual with pre-existing cell-mediated immunity. This immunity prevents systemic dissemination but allows for local persistence of the bacilli, resulting in a paucibacillary lesion that is difficult to diagnose microbiologically. This case represents an extreme spectrum of neglected disease, where a two-decade diagnostic delay allowed for extensive local spread via autoinoculation and contiguous extension, culminating in a severe and debilitating clinical presentation. The diagnosis often relies on clinicopathological correlation and the response to anti-tubercular therapy. Conclusion: This case report highlights the severe consequences of delayed diagnosis and inadequate management of TVC. It underscores the critical importance of maintaining a high index of clinical suspicion for chronic verrucous lesions, particularly in TB-endemic regions, to prevent significant long-term morbidity and permanent disability.